A novel secreted-cAMP pathway inhibits pulmonary hypertension via a feed-forward mechanism. Issue 8 (14th September 2019) - Jones, Carly; Bisserier, Malik; Bueno-Beti, Carlos; Bonnet, Guillaume; Neves-Zaph, Susana; Lee, Sang-Yong; Milara, Javier; Dorfmüller, Peter; Humbert, Marc; Leopold, Jane A; Hadri, Lahouaria; Hajjar, Roger J; et al.
Abstract: Aims: Cyclic adenosine monophosphate (cAMP) is the predominant intracellular second messenger that transduces signals from Gs-coupled receptors. Intriguingly, there is evidence from various cell types that an extracellular cAMP pathway is active in the extracellular space. Herein, we investigated the role of extracellular cAMP in the lung and examined whether it may act on pulmonary vascular cell proliferation and pulmonary vasculature remodelling in the pathogenesis of pulmonary hypertension (PH). Methods and results: The expression of cyclic AMP-metabolizing enzymes was increased in lungs from patients with PH as well as in rats treated with monocrotaline and mice exposed to Sugen/hypoxia. We report that inhibition of the endogenous extracellular cAMP pathway exacerbated Sugen/hypoxia-induced lung remodelling. We found that application of extracellular cAMP induced an increase in intracellular cAMP levels and inhibited proliferation and migration of pulmonary vascular cells in vitro . Extracellular cAMP infusion in two in vivo PH models prevented and reversed pulmonary and cardiac remodelling associated with PH. Using protein expression analysis along with luciferase assays, we found that extracellular cAMP acts via the A2 R/PKA/CREB/p53/Cyclin D1 pathway. Conclusions: Taken together, our data reveal the presence of an extracellular cAMP pathway in pulmonary arteries that attempts to protect the lung during PH, and suggest targeting of the extracellular cAMP signalling pathway to limit pulmonary vascular remodelling and PH. Graphical Abstract: